Yasinan Rabu Wage Masyarakat Dukuh Sambong Bojonegoro (Studi Living Qur’an) - Laili Nur Hidayah; Adrika Aini (Tebuireng: Journal of Islamic Studies and Society, 2021)
The Living Quran is a study of the Quranic text that lives in society as a phenomenon by accepting, responding, utilizing or using it. This paper aims to describe the meaning and values contained in the Yasinan Wednesday Wage tradition in Sambong Kedungrejo. This paper uses a ethnographic approach through living Quran reseach accompanied by a qualitative descriptive method, also focuses on Clifford Geerts' Cultural Interpretation theory. Data collection was carried out through field research by means of observation, interviews, and documentation. This tradition was formed to make people believe and pious, as well as strengthen Ukhuwah Islamiyah. The Yasinan tradition is complete with tahlil, prayers, and lectures every Wednesday wage in the mosque or prayer room gradually. There are several symbols in this tradition, so that it creates an aura of truth which then creates a unique motivation and feeling that will look realistic. So this Yasinan tradition becomes the soul satisfying the longing for his Robb. This tradition is wrapped in a unique way without forgetting the concept of preaching Islam. The symbols in this study, namely the reading of Surat Yasin, reciting Tahlil along with the prayer, Qiroah, Chanting Sholawat Nabi, welcome speech and ending with a lecture by local Kyai.